Perinatal Hypoxia and Immune System Activation in Schizophrenia Pathogenesis: Critical Considerations During COVID-19 Pandemic - Kawikova, I; Hakenova, K; Lebedeva, M; Kleteckova, L; Jakob, L; Spicka, V; Wen, L; Spaniel, F; Vales, K (Physiological research, 2024)
Schizophrenia, a severe psychiatric, neurodevelopmental disorder affecting about 0.29-1 % of the global population, is characterized by hallucinations, delusions, cognitive impairments, disorganized thoughts and speech, leading to significant social withdrawal and emotional blunting. During the 1980s, considerations about diseases that result from complex interactions of genetic background and environmental factors started to appear. One of the critical times of vulnerability is the perinatal period. Concerning schizophrenia, obstetric complications that are associated with hypoxia of the fetus or neonate were identified as a risk. Also, maternal infections during pregnancy were linked to schizophrenia by epidemiological, serologic and genetic studies. Research efforts then led to the development of experimental models testing the impact of perinatal hypoxia or maternal immune activation on neurodevelopmental disorders. These perinatal factors are usually studied separately, but given that the models are now validated, it is feasible to investigate both factors together. Inclusion of additional factors, such as metabolic disturbances or chronic stress, may need to be considered also. Understanding the interplay of perinatal factors in schizophrenia's etiology is crucial for developing targeted prevention and therapeutic strategies.
Keywords: hypoxie plodu; Animals; imunitní systém; Pregnancy Complications, Infectious; Female; Hypoxia; novorozenec; Immune System; ženské pohlaví; lidé; Infant, Newborn; těhotenství; COVID-19; schizofrenie; hypoxie; infekční komplikace v těhotenství; Schizophrenia; Fetal Hypoxia; zvířata; Pregnancy; Humans